The development of trunk control and its relation to reaching in infancy: a longitudinal study - Rachwani, Jaya; Santamaria, Victor; Saavedra, Sandra L.; Woollacott, Marjorie H. (Frontiers in Human Neuroscience, 2015)
The development of reaching is crucially dependent on the progressive control of the trunk, yet their interrelation has not been addressed in detail. Previous studies on seated reaching evaluated infants during fully supported or unsupported conditions; however, trunk control is progressively developed, starting from the cervical/thoracic followed by the lumbar/pelvic regions for the acquisition of independent sitting. Providing external trunk support at different levels to test the effects of controlling the upper and lower regions of the trunk on reaching provides insight into the mechanisms by which trunk control impacts reaching in infants. Ten healthy infants were recruited at 2.5 months of age and tested longitudinally, until 8 months. During the reaching test, infants were placed in an upright seated position and an adjustable support device provided trunk fixation at pelvic and thoracic levels. Kinematic and electromyographic data were collected. Results showed that prior to independent sitting, postural instability was higher when infants were provided with pelvic compared to thoracic support. Associated reaches were more circuitous, less smooth and less efficient. Associated with this instability, there was increased postural muscle activity and arm muscle co-activation. Differences between levels of support were not observed once infants acquired independent sitting. These results suggest that trunk control is acquired in a segmental sequence across the development of upright sitting, and it is tightly correlated with reaching performance.